Impact of Sex on the Nonmotor Symptoms and the Health-Related Quality of Life in Parkinson’s Disease - Márton Kovács; Attila Makkos; Zsuzsanna Aschermann; József Janszky; Sámuel Komoly; Rita Weintraut; Kázmér Karádi; Norbert Kovács (Parkinson's Disease)
Background. Female Parkinson’s disease (PD) patients seem to experience not only more severe motor complications and postural instability but also more pronounced depression, anxiety, pain, and sleep disturbances. Objective. The aim of the present study was to evaluate the role of sex as a possible independent predictor of HRQoL in PD. Methods. In this cross-sectional study, 621 consecutive patients treated at the University of Pécs were enrolled. Severity of PD symptoms was assessed by MDS-UPDRS, UDysRS, Non-Motor Symptoms Scale, PDSS-2, Hamilton Anxiety Scale, Montgomery-Asberg Depression Rating Scale, Lille Apathy Rating Scale, and Addenbrooke Cognitive Examination. HRQoL was assessed by PDQ-39 and EQ-5D. Multiple regression analysis was performed to estimate the PDQ-39 and EQ-5D index values based on various clinical factors. Results. Although females received significantly lower dosage of levodopa, they had significantly more disabling dyskinesia and worse postural instability. Anxiety, pain, sleep disturbances, and orthostatic symptoms were more frequent among females while sexual dysfunction, apathy, and daytime sleepiness were more severe among males. Women had worse HRQoL than men (EQ-5D index value: 0.620±0.240 versus 0.663±0.229, p=0.025, and PDQ-39 SI: 27.1±17.0 versus 23.5±15.9, p=0.010). Based on multiple regression analysis, sex was an independent predictor for HRQoL in PD. Conclusions. Based on our results, female sex is an independent predictor for having worse HRQoL in PD.